Laying the foundations of a more conscious society? How vendors, consumers and organizers socially construct farmers’ markets in Bogotá, Colombia - Gütschow, Malin; Feola, Giuseppe (Revista Colombiana de Ciencias Sociales, 2022)
This study examines how vendors, customers, and organizers socially construct agroecological farmers markets (FM) in Bogotá. Using a multi-method approach entailing structured and unstructured interviews, descriptive statistics, and ethnographic content analysis, the study shows how the actors situate FM in relation to debates on sustainability, rural development, and alternative agri-food systems in Colombia. The results demonstrate that vendors, customers, and organizers often hold largely similar perspectives on FM and their relations with the dominant food system. Specifically, they conceive of FM as an alternative to the dominant food system and experience them as spaces in which utilitarian relations are put aside in favour of alternative values and practices, which include care for other human and non-human beings and limited economic competition. Furthermore, FM simultaneously function as protective spaces for peasant knowledge and culture and connectors between rurality and urbanity. Finally, this study shows that FM cannot be fully understood within the sectoral scope of sustainable agriculture, or rural development; rather, they represent an attempt to lay the foundations of a more conscious society that vendors, customers, and organizers want to help come into being.